Modelos cosmológicos en la Ciencia Escolar. Aportes desde la historia de la ciencia para su enseñanza – aprendizaje - Camacho-González, Johanna Patricia; Espinoza-Cona, Carolina Eugenia (Revista Científica, 2016)
This study seek to examine the explanatory models of secondary school students, concerning the solar system before and after an didactic intervention involving the history of science related to cosmological models, based from the cognitive model of science (Giere, 1992). The research took place in two stages: a. Design and validation of a didactic unit according to the constructivist learning cycle (Sanmartí, 2000); and b. Identification and comparison of the explicative models before and after the proposed educational intervention. The main findings expose that the role of the history of science is relevant for the construction of more complex and variable, dynamic explicative models related to cosmological theory. Such models were strongly characterized by the inclusion of novel elements, a strong correlation between several celestial bodies and to expose a more specialized language.